2020
DOI: 10.1377/hlthaff.2019.00981
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Community Health Worker Program Addresses Unmet Social Needs And Generates Positive Return On Investment

Abstract: Interventions that address socioeconomic determinants of health are receiving considerable attention from policy makers and health care executives. The interest is fueled in part by expected returns on investment. However, many current estimates of returns on investment are likely overestimated, because they are based on pre-post study designs that are susceptible to regression to the mean. We present a return-on-investment analysis that is based on a randomized controlled trial of Individualized Management fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
120
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(120 citation statements)
references
References 25 publications
0
120
0
Order By: Relevance
“…Community‐based doulas typically provide frequent in‐home visits, as well as services similar to those provided by community health workers: helping patients access social services (e.g., subsidized housing, nutrition assistance programs, intimate partner violence interventions) and navigate the complex components of care during and after pregnancy, and bridging communication divides between providers and patients 22,51,52 . While randomized controlled trials assessing the impact of community‐based doulas on birth outcomes are lacking, there is a substantial body of high‐quality evidence supporting the role of community health workers in improving health outcomes among historically marginalized populations 53–56 …”
Section: The Benefits Of Doula Carementioning
confidence: 99%
See 1 more Smart Citation
“…Community‐based doulas typically provide frequent in‐home visits, as well as services similar to those provided by community health workers: helping patients access social services (e.g., subsidized housing, nutrition assistance programs, intimate partner violence interventions) and navigate the complex components of care during and after pregnancy, and bridging communication divides between providers and patients 22,51,52 . While randomized controlled trials assessing the impact of community‐based doulas on birth outcomes are lacking, there is a substantial body of high‐quality evidence supporting the role of community health workers in improving health outcomes among historically marginalized populations 53–56 …”
Section: The Benefits Of Doula Carementioning
confidence: 99%
“…22,51,52 While randomized controlled trials assessing the impact of community-based doulas on birth outcomes are lacking, there is a substantial body of highquality evidence supporting the role of community health workers in improving health outcomes among historically marginalized populations. [53][54][55][56] A 2019 analysis of several community-based doula programs compared health outcomes between a racially and ethnically diverse sample (47% Hispanic, 33% Black) of 592 low-income individuals who received doula services and a comparison sample of participants from the population-based Pregnancy Risk Assessment Monitoring System (PRAMS). 20 Compared with their counterparts in the PRAMS group, Black mothers enrolled in communitybased doula programs were more likely to be exclusively breastfeeding at six weeks (71% vs. 56%), three months (52% vs. 38%) and six months (39% vs. 7%).…”
Section: The Benefi Ts Of Doula Carementioning
confidence: 99%
“…The perception that for some partnerships, clinical partners did not place sufficient value on services delivered by non-physician staff (including CHWs) or through community-based organizations is a challenge to a referral-based program and more broadly to a sense of trust, reciprocity, and joint action within a partnership. Service delivery by CHWs—particularly in the context of care delivery by multidisciplinary teams—provides an important opportunity to improve health equity and reduce healthcare costs to payers ( 52 , 53 ). The network contributions identified in this study can serve as a useful starting point for defining relationships in quantitative social network analyses to describe the functioning and impact of community-clinical partnerships delivering preventive EBPs.…”
Section: Discussionmentioning
confidence: 99%
“…We estimate that the average cost of the CHW intervention across all three trials was approximately $1499 per patient, per year (Table ). A detailed analysis of expenditures and cost savings associated with the IMPaCT CHW intervention, using data from Trial 2, has been reported elsewhere 20 …”
Section: Methodsmentioning
confidence: 99%